اليقظة العقلية وعلاقتها بالتدفق النفسي وسلوك المخاطرة لدى طلبة كلية التربية - جامعة المنصورة - معوض، دينا صلاح الدين إبراهيم (جامعة المنصورة - مركز تطوير الأداء الجامعي, 2021)
The aim of this research is to reveal the differences between low and high mindfulness in psychological flow and risk taking behavior among students of the College of Education, and to determine the nature of the relationship between mindfulness and both psychological flow and risk taking behavior they have, by applying three measures prepared by the researcher on a sample of (450) A male and a female student from the fourth year of the Faculty of Education at Mansoura University, including (228) male and (222) female students. The results showed that there are fundamental differences between high and low mindfulness in psychological flow in favor of high mindfulness and in risk taking behavior in favor of low mindfulness, and there is no significant effect on the type of students, there academic specialization and the interaction between them on the level of mental alertness, as shown. The results, therefore, indicate the existence of a positive correlation significant between students ‘scores on the scale of mindfulness and psychological flow, and a significant correlational relationship between students’ scores on the scale of mindfulness and risk-taking behavior.
هدف هذا البحث إلى الكشف عن الفروق بين منخفضي ومرتفعي اليقظة العقلية في التدفق النفسي وسلوك المخاطرة لدى طلبة كلية التربية، وتحديد طبيعة العلاقة بين اليقظة العقلية وكل من التدفق النفسي وسلوك المخاطرة لديهم، وذلك بتطبيق ثلاثة مقاييس من إعداد الباحثة على عينة بلغ قوامها (450) طالب وطالبة من الفرقة الرابعة بكلية التربية بجامعة المنصورة منهم (228) طالبا و(222) طالبة، وباستخدام اختبار (ت) وتحليل التباين ثنائي الاتجاه ومعامل ارتباط بيرسون، وأسفرت النتائج عن وجود فروق جوهرية بين اليقظة العالية والمنخفضة في التدفق النفسي لصالح اليقظة العالية وسلوك المخاطرة لصالح منخفضي اليقظة العقلية في التدفق النفسي لصالح مرتفعي اليقظة العقلية، وفي سلوك المخاطرة لصالح ضعف اليقظة، ولا يوجد تأثير معنوي على نوع الطلبة وتخصصهم الأكاديمي والتفاعل بينهما على مستوى اليقظة العقلية، كما أظهرت النتائج كذلك عن وجود علاقة ارتباطية موجبة دالة بين درجات الطلبة على مقياس اليقظة العقلية والتدفق النفسي، وعلاقة ارتباطية سالة دالة بين درجات الطلبة على مقياس اليقظة العقلية وسلوك المخاطرة.
Keywords: طلبة الجامعات -- علم النفس الايجابي -- الصحة النفسية